The relationship between sustainability and contemporary fashion design: an analysis of the segment jeanswear - Moura, Mónica (2013)
Fashion is one of the reflexes that best expresses the dynamics of contemporary, and sustainability is one of the questioner agents of the concept and approach of fashion and fashion design, this way, the purpose of this paper is to present a critical analysis of the relationship between fashion and sustainability, with the aim of comparing and verifying the discourses of advocated by jeanswear segment companies and the development of its garments, called “sustainable”. The reasoning begins from literature review of these areas added to field research with structured interviews, application of questionnaires and later analysis of companies.